Autoritatif Hukum Penentuan Awal Bulan di Indonesia - Fajri Assiddiq (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2020)
Determination of the beginning of the lunar month conducted by the government to realize the benefit of Muslims. The law has stipulated that issues of good quality are necessary and justified by the interference of ulil amri, the government. This was done in order to create public benefit. The government in setting the beginning of the month is not because of authority but authoritative. This means that the authority is that the government is only based on the authority of power while authoritative is based on shar'i arguments.